PENGARUH BUDAYA ORGANISASI TERHADAP KOMITMEN ORGANISASI PADA PEGAWAI KANTOR CAMAT - Anas Tri Yanto; Jaenab Jaenab (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
This research was used to see the effect of organizational culture on organizational commitment in east rasanae district office staff. The quatitative method used in this study which shows cause and effect. The sample used is employees. Observation, questionnaire and documentation are data collection used. The data analysis thechnique used in this study is a simple linear regression analysis using IBM SPSS 21 software. The results of the study show that: organizational commitment in east rasanae district office staff.